DIFFERENT AMOUNT OF THROMBOCYTES ON BLOOD STORAGE FOR 24 HOURS IN ROOM AND REFRIGERATOR - Lestari, Ayu Indah (Journal of Vocational Health Studies, 2019)
Background: Storage is a pre-analytic part that plays a role in maintaining cell quality functionally. Examination of platelet count is influenced by pre-analytic factors, namely time and temperature since specimen collection so that the specimen storage guidelines are needed to obtain accurate laboratory results. Delays in examinations often occur and are caused by the lack of medical personnel, heavy volume of work, or non-technical problems that occur during examination. Purpose: Analyze the effect of storing blood samples at room temperature (18-24oC) and refrigerator (2-8oC) for 24 hours on platelet count. Method: Analytical observations, 30 samples with normal criteria, thrombocytosis, and thrombocytopenia that were examined at Laboratorium Patologi Klinik RSU Haji Surabaya. The method used is analytical observations and the study used a different test of friedman with SPSS 16.0 program to determine whether there is a significant difference in platelet count in blood samples at room temperature and refrigerator temperature for 24 hours with the initial examination. Result: The results of the friedman test analysis of the differences in the results of platelet count for 30 samples showed significant differences with sig. (2-tailed) of 0.00 (p <0.05). Conclusion: There was a significant difference between the results of the platelet count at the beginning of the examination with a delay in the refrigerator storing temperature (2-8oC) and room storing temperature (18-24oC) for 24 hours.